Macroeconomic Theory and Macroeconomic Pedagogy: A response to some criticisms - Giuseppe Fontana; Mark Setterfield (Intervention. European Journal of Economics and Economic Policies, 2010)
First paragraph: It is with great pleasure that we participate in this Special Forum discussion of our Macroeconomic Theory and Macroeconomic Pedagogy (MTMP) (Fontana/Setterfield 2009). Before discussing the comments by Claudio Sardoni and Sebastian Dullien, we would first like to outline the substance of MTMP. The book contains sixteen chapters written by active research scholars with an introduction by ourselves and a foreword by C.E. Walsh. The main purpose of the book is to present contemporary macroeconomic theory – specifically, New Consensus Macroeconomics (NCM) and alternatives to the NCM – to introductory and intermediate undergraduate students. To this end, the chapters portray the most recent developments in macroeconomics in a simple and diagrammatic way. Many of the chapters are intended for direct consumption by students, and are therefore suitable for introduction into the classroom. Others are aimed at our colleagues, with a view to influencing the way instructors think about macroeconomic theory, and hence what they will subsequently seek to teach to their students. In our view the book has two main merits. First, MTMP moves beyond the standard IS-LM model and some of its theoretical limitations, including the hypotheses of a fixed money supply, and exogenous expectations. Secondly, it builds on successful pedagogical features of previous models (such as graphical analysis of policy choices) to promote a better understanding of real world issues, including the recent financial crisis and related recession.
Keywords: 330